UPAYA GURU DALAM MEMBINA KEMATANGAN SOSIAL ANAK DI TK NEGERI PEMBINA PONTIANAK UTARA - Nurlita Sari; Aloysius Mering; Desni Yuniarni (Universitas Tanjungpura, 2019)
Abstract The background of this research is the reality of children’s underdeveloped social ripeness. This fact makes the researcher wants to know what the teacher’s effort to cultivate the social ripeness of children ages 5 to 6 in TK Negeri Pembina North Pontianak is. The general purpose of this research is to describe the effort of the teacher in cultivating the social ripeness of the children ages 5 to 6 in TK Negeri Pembina North Pontianak. The research uses descriptive method with qualitative approach. The background of this research is the reality of children’s underdeveloped social ripeness. This fact makes the researcher wants to know what the teacher’s effort to cultivate the social ripeness of children ages 5 to 6 in TK Negeri Pembina North Pontianak is. The main purpose of this research is to describe the effort of the teacher in cultivating the social ripeness of the children ages 5 to 6 in TK Negeri Pembina North Pontianak. The research uses descriptive method with qualitative approach. It is expected that the teacher gives equal treatment to all children so that they will be able to develop optimally. Keywords: Teacher’s Effort, Social Ripeness